Guna dan citra sebagai wujud kreativitas dalam arsitektur nusantara: Studi kasus arsitektur Tongkonan Toraja, Mamasa dan Batak Toba - Josephine Roosandriantini (Universitas Islam Negeri Sunan Ampel Surabaya, 2020)
Nusantara architecture, which is the result of creative ideas from the Nusantara people, tends to be created with simple materials and equipment. However, the Nusantara architecture, which comes with its ancient identity, does not mean that it has no creative value. This study explores the application of Mangunwijaya's